International perspectives on social work and political conflict - Duffy, Joe; Campbell, Jim, 1956-; Tosone, Carol (Abingdon, Oxon ; New York, NY : Routledge, 2019)
International Perspectives on Social Work and Political Conflict provides an important basis for readers to recognise and understand the unique and specialist role that social workers have played and continue to play in international contexts of political conflict. Social workers make an important contribution in these difficult and sometimes dangerous situations across all continents. This book highlights the importance of social work in these very challenging contexts. The first part of this book includes four chapters that summarise the existing knowledge base. The second part focuses on a case study of Northern Ireland where, for the first time, a detailed examination of the social work role was completed which involved researching the views of social work practitioners, managers and educators. Part three then draws together international experts in the field who have written chapters on those regions where social workers have been dealing with long standing periods of political conflict. At a time when violent conflagrations are currently a feature of many countries and regions across the continents of the world, this book offers a critical view of the social work role in these contexts and should thus be considered essential reading for all social work academics, students and professionals working in conflict-affected societies.
7. Social work and the Cyprus problem: The challenges of reconciliation in de facto divided and crisis-ridden societiesIntroduction; Cyprus; Social work, colonialism and conflict in Cyprus: a paradoxical relationship; The historical evolution of social work in Cyprus; Committee on Missing Persons (CMP): the hidden force of social work beneath the success?; Equality and social questions in the Cyprus settlement: social workers, welfare and action; Thinking ahead: future research agenda; Conclusion; References; 8. The Israeli Context; Introduction; Context; Domestic Realities
OCLC-licensed vendor bibliographic record.
Keywords: SOCIAL SCIENCE / Social Work; SOCIAL SCIENCE / Violence in Society; Social service; War -- Social aspects; Social conflict